2018
DOI: 10.1098/rstb.2017.0327
|View full text |Cite
|
Sign up to set email alerts
|

New functions for the proprioceptive system in skeletal biology

Abstract: Muscle spindles and Golgi tendon organs (GTOs) are two types of sensory receptors that respond to changes in length or tension of skeletal muscles. These mechanosensors have long been known to participate in both proprioception and stretch reflex. Here, we present recent findings implicating these organs in maintenance of spine alignment as well as in realignment of fractured bones. These discoveries have been made in several mouse lines lacking functional mechanosensors in part or completely. In both studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 109 publications
1
33
0
1
Order By: Relevance
“…Finding similar joint abnormalities in mutants for the proprioceptive system regulators Runx3 and Egr3 confirms the role of this system in hip joint morphogenesis. Overall, this work expands our emerging concept 50 and firmly establishes the proprioceptive system as a central regulator of skeletal integrity and Piezo2 as a key component in this regulation (Fig. 10).…”
Section: Discussionsupporting
confidence: 68%
“…Finding similar joint abnormalities in mutants for the proprioceptive system regulators Runx3 and Egr3 confirms the role of this system in hip joint morphogenesis. Overall, this work expands our emerging concept 50 and firmly establishes the proprioceptive system as a central regulator of skeletal integrity and Piezo2 as a key component in this regulation (Fig. 10).…”
Section: Discussionsupporting
confidence: 68%
“…The observation that the strong VM-VL correlation was consistent across task conditions might suggest that these patterns are produced by lower-level sensorimotor systems, potentially within the spinal cord. For example, last order spinal interneurons might branch to activate both VM and VL motoneurons (15,55) or be strongly coordinated by feedback from sensory afferents (56) conveying information about patellar loading via joint receptors (57,58) or muscle proprioceptors (59,60). However, previous work has suggested that the strong covariation between VM and VL motor units is due to both cortical and spinal systems (15,16), suggesting that this covariation may result from distributed processing in multiple areas of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The upright posture is made possible by proprioceptive system based on cortical, subcortical, and medullary integration of multisensorial information, especially somesthetic input (Munoz-Rubke et al, 2017 ; Sim et al, 2018 ). Proprioceptive system provides direct information on position and movements of body segments (Blecher et al, 2018 ). The gait parameters of AIS patients were investigated, and somatosensory dysfunction in AIS patients showed to have an impact on dynamic balance control (Lao et al, 2008 ).…”
Section: The Function Of the Lbx1 Gene In Interneuron Developmentmentioning
confidence: 99%